In vivo kinematics of the thumb during flexion and adduction motion: Evidence for a screw‐home mechanism. Issue 7 (19th September 2016) - D'Agostino, Priscilla; Dourthe, Benjamin; Kerkhof, Faes; Stockmans, Filip; Vereecke, Evie E.
ABSTRACT: The thumb plays a crucial role in basic hand function. However, the kinematics of its entire articular chain have not yet been quantified. Such investigation is essential to improve our understanding of thumb function and to develop better strategies to treat thumb joint pathologies. The primary objective of this study is to quantify the in vivo kinematics of the trapeziometacarpal (TMC) and scaphotrapezial (ST) joints during flexion and adduction of the thumb. In addition, we want to evaluate the potential coupling between the TMC and ST joints during these tasks. The hand of 16 asymptomatic women without signs of thumb osteoarthritis were CT scanned in positions of maximal thumb extension, flexion, abduction, and adduction. The CT images were segmented and three‐dimensional surface models of the radius, scaphoid, trapezium, and the first metacarpal were created for each thumb motion. The corresponding rotations angles, translations, and helical axes were calculated for each sequence. The analysis shows that flexion and adduction of the thumb result in a three‐dimensional rotation and translation of the entire articular chain, including the trapezium and scaphoid. A wider range of motion is observed for the first metacarpal, which displays a clear axial rotation. The coupling of axial rotation of the first metacarpal with flexion and abduction during thumb flexion supports the existence of a screw‐home mechanism in the TMC joint. In addition, our results point to a potential motion coupling between the TMC and ST joints and underline the complexity of thumb kinematics. © 2016 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 35:1556–1564, 2017. Abstract : The thumb plays a crucial role in basic hand function. This study quantifies the in vivo kinematics of the trapeziometacarpal and scaphotrapezial joints of 16 asymptomatic women during flexion and adduction of the thumb. The analysis shows that both motions result in a three‐dimensional rotation and translation of the entire articular chain. The coupling of axial rotation of the first metacarpal with flexion and abduction during thumb flexion supports the existence of a screw‐home mechanism in the TMC joint.